Predictable anconeus dimensions with limited influence from patient size: implications for surgical planning and applications - Connor C. Park, BS; Julia R. Wieland, BS; Ryan D. DeAngelis, MD; Manuel E. Cevallos, MD; Andrew M. Choo, MD (JSES Reviews, Reports, and Techniques)
Background: Surgeons can manipulate the anconeus muscle for soft tissue coverage around elbow wounds or mobilize it during distal humerus fractures to improve visualization and potentially obviate the need for an olecranon osteotomy. While anatomical studies have explored the anconeus muscle's dimensions, it is unclear whether it scales consistently with nearby structures or changes markedly with subject size. Methods: Thirty assessments were conducted on 15 cadavers. The triangular muscle's borders are defined as follows: the superior border extends from the lateral epicondyle of the humerus to the ulna near the olecranon; the lateral inferior border runs from the lateral epicondyle to the muscle's insertion on the proximal and middle thirds of the ulna; and the base corresponds to the insertion along the ulna. All measurements of the anconeus were performed with the elbow flexed to 90°. α was assigned 0.05. Results: Average superior border measured 2.51 cm ± 0.36 cm, lateral inferior border 8.05 cm ± 1.03 cm, and base 7.32 cm ± 0.94 cm. The average width of the distal humerus was 6.61 cm ± 0.66 cm. Patients ranged from 152 cm to 185 cm in height and 59-82 kg in weight. A moderate positive correlation was observed between the lateral inferior border and the width of the distal humerus (ρ = 0.56; r2 = 0.31; P = .001) and between the base and the width of the distal humerus (ρ = 0.51; r2 = 0.265; P = .004). A low positive correlation was observed between the superior border and the width of the distal humerus. A moderate correlation was found between patient height and only the lateral inferior border (ρ = 0.54; r2 = 0.289; P = .002). Low correlations were noted between the other borders and height, length or radius and lateral inferior border, and length of ulna and lateral inferior border. Poor correlations were found between all remaining borders with the lengths of the radius, humerus, ulna, and triceps (lateral and long head). Discussion: The weak associations with other structures suggest that the size of the anconeus is less affected by the dimensions of nearby musculoskeletal elements, indicating a more consistent anatomical size compared to muscles that typically scale with bone length or physical activity. The anconeus muscle's consistent size offers surgeons a reliable solution for addressing soft tissue defects in procedures around the elbow, even in smaller individuals. Its predictable dimensions ensure a consistent and unobstructed visualization of the distal humerus during procedures like open reduction and internal fixation, regardless of patient size.